New Realities, Mobile Systems and Applications Proceedings of the 14th IMCL Conference - Auer, Michael E.; Tsiatsos, Thrasyvoulos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book devotes to new approaches in interactive mobile technologies with a focus on learning. Interactive mobile technologies are today the core of many if not all fields of society. Not only the younger generation of students expects a mobile working and learning environment. And nearly daily new ideas, technologies and solutions boost this trend. To discuss and assess the trends in the interactive mobile field are the aims connected with the 14th International Conference on Interactive Mobile Communication, Technologies and Learning (IMCL2021), which was held online from 4 to 5 November 2021. Since its beginning in 2006, this conference is devoted to new approaches in interactive mobile technologies with a focus on learning. Nowadays, the IMCL conferences are a forum of the exchange of new research results and relevant trends as well as the exchange of experiences and examples of good practice. Interested readership includes policy makers, academics, educators, researchers in pedagogy and learning theory, school teachers, learning Industry, further education lecturers, etc.
Problems And Prospects Of Using Remote Learning Technologies In Different Countries -- Mobile Technology for Learning During Covid-19: Opportunities, Lessons, and Challenges -- The Abrupt Shift To Full Online And Then Blended Learning At A French Engineering School: Difficulties And Practices, Reaction And Adaptation -- Parent Perceptions of Mobile Device Use Among Preschool-Aged Children in Greece -- Mobile Simulation Game for Learning Theory of Constraints Fundamentals -- Exploring Pre-schoolers Feelings during Online Learning with Elements of Educational Neuroscience -- Online Learning, Students Assessment and Educational Neuroscience -- Cloud Technologies Application At English Language Studying And Self-Control Realization For Maritime Branch Specialists -- Work-in-Progress: Development Of VCDLN Model As Implementation of Distance Learning In The Era of The Covid-19 Pandemic in Indonesia -- Rethinking Audio-haptic Perceptual Immersion from In-person to Remote Testing During Covid-19 -- Work-in-progress About Dynamicity as a Foundation for AMI, a Mobile Intelligent and Adaptative Learning System.
Keywords: Cooperating objects (Computer systems).; Engineering Data processing; Cyber-Physical Systems; Data Engineering; Mobile communication systems in education -- Congresses